Hubungan Faktor Genetik dan Asupan Energi dengan Kejadian Obesitas - Rizky Aulia Rachma; Trias Mahmudiono (Media Gizi Kesmas, 2023)
Background: Obesity occurs due to an imbalance between the amount of energy intake into the body and the energy needed by the body. Genetic factors and the amount of daily energy intake are some of the factors that cause obesity. Objectives: This study aims to determine the relationship between genetic factors and energy intake with the incidence of obesity. Methods: This research method was descriptive quantitative. The population in this study were students of SMP Negeri 24 Surabaya who had overweight and obese status. Sampling using Lemeshow formula with a sample size of 27 students. The instruments used were questionnaires and 3x 24h recall. Results: The results of the study using the Pearson test showed a relationship between genetic factors and the incidence of obesity p-value = 0.030 and a relationship between energy intake and the incidence of obesity p-value = 0.042 Conclusions: Obesity can occur due to genetic factors and excessive energy intake.